Prospective Teachers’Views about Creating Websites for Social Studies Teaching in Distance Education - Akyol, Canan; Avcı, Görkem; Dikicigil, Özdemir; Avcı, Görkem (My University, 2021)
The present study aims to investigate prospective teachers’ views about creating websites for social studies teaching in distance education. To this end, the study employed the case study method, one of the qualitative research methods. The study group consisted of prospective social studies and classroom teachers studying in the 2019-2020 academic year at the Faculty of Education of a state university located in the Black Sea Region. The study was conducted in two phases: the first phase was carried out with 112 prospective teachers and the second with 12. Data were collected by means of structured and semi-structured interviews and were analyzed by content analysis. Data analysis revealed that websites were a part of the learning-teaching process, that it was important to use websites as educational tools, that websites enabled technology to be integrated into education, that websites enabled the inclusion of up-to-date content for effective teaching of social studies, and that websites provided students with easy access to knowledge through fun learning environments. Based on the results, it can be recommended that the creation and use of websites for the social studies course should be promoted among both working and prospective teachers and that social studies lessons can be taught more effectively with personal educational websites that contain up-to-date, fun, and interactive teaching materials
Keywords: Eğitim; Eğitim Araştırmaları